Pengaruh Kepuasan Konsumen Terhadap Pendapatan Home Industri Almah Cake Di Kaliabang Nangka Kota Bekasi - Nahason Sitohang; Muslimin Muslimin (Jurnal of Management and Social Sciences, 2023)
This research is a quantitative research with the title: "The Influence of Consumer Satisfaction on the Income of the Almah Cake Home Industry in Kaliabalng Nangkal, Bekasi City" in 2023. The aim of this research is to find out how much influence consumer satisfaction has on the income of the Almah Cake Home Industry in Kaliabang Nangka Bekasi city. Data collection techniques used methods, interviews and documentation, with a population of 35 people who then analyzed the data using validation tests, reliability tests, classical assumption tests, normality tests, heteroscedasticity tests and simple linear regression analysis. The research results obtained an F test value of 9.440 which shows that there is an influence of the independent variable on the dependent variable. This means that the hypothesis that the consumer satisfaction variable has an influence of 94.4% on the income of the almah cake home industry in Kaliabang Nangka, Bekasi City and the remaining 5.6% is influenced by other variables that were not studied. The results show that the consumer satisfaction variable (X) appears to have t-bit = 3.073 > t-table = 2.034. The variables of service, price, product quality, promotion together have a significant influence on the income of the Almah Cake Home Industry.